2021
DOI: 10.1007/s10706-020-01663-1
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Algorithm for Exponential Curve Model of Single Pile Bearing Capacity

Abstract: The ultimate bearing capacity of single pile is very important to engineering safety, so correctly predicting its value becomes an important part of engineering safety. Based on the traditional exponential curve model, a parameter optimization algorithm of the exponential curve model of single pile bearing capacity, which combines the golden section method and the linear least square method, is proposed. In order to verify the reliability of the proposed optimization algorithm, the measured data of the buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The previous studies have shown that the hyperbolic method (HM) gave very good forecasts of ultimate primary settlements for both laboratory oedometer tests and field settlements for clays with vertical drains [51,52]. In addition, the exponential curve method (ECM) has been shown to be reasonable and correct in the forecast of vertical ultimate bearing capacity of single pile [21] and the sure part of the roadbed settlement [53]. However, the applicability of these two most commonly used EFMs is worth discussing for the forecast of the PVD-assisted staged riprap filling foundation in deep marine soft soils.…”
Section: Empirical Formula Methods (Efm)mentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies have shown that the hyperbolic method (HM) gave very good forecasts of ultimate primary settlements for both laboratory oedometer tests and field settlements for clays with vertical drains [51,52]. In addition, the exponential curve method (ECM) has been shown to be reasonable and correct in the forecast of vertical ultimate bearing capacity of single pile [21] and the sure part of the roadbed settlement [53]. However, the applicability of these two most commonly used EFMs is worth discussing for the forecast of the PVD-assisted staged riprap filling foundation in deep marine soft soils.…”
Section: Empirical Formula Methods (Efm)mentioning
confidence: 99%
“…The exponential curve describes the time dependence of settlement using an exponential formula as shown in Equation ( 2) [21]:…”
Section: Exponential Curve Methods (Ecm)mentioning
confidence: 99%
See 1 more Smart Citation
“…From the test and ANSYS finite element simulation results, an F-CEP pile will bend first and then overturn under a horizontal load. Accordingly, the force mode of the F-CEP pile is determined [30,31], as shown in Figure 11.…”
Section: Calculation Mode For Single Pile-bearing Capacitymentioning
confidence: 99%
“…It is difficult to perceive the ultimate bearing capacity intuitively from such curves. For this scenario, many interpretation methods based on graphical construction, mathematical model and settlement limit have been proposed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%